Influence Learning Strategies to Enhance Physical Condition and Focus in Young Badminton Players During Matches - Hasbunallah Arief Saleh; Hasyim Hasyim; Muhammad Mifta Fauzan (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study examines the influence of physical condition and concentration on short-serve performance in badminton among elementary school students. The research adopts a descriptive quantitative approach, involving two independent variables, physical condition and concentration, and one dependent variable, short-serve performance. The study was conducted in an elementary school setting with a population of all students, and simple random sampling technique using the lottery method was applied to select 30 students as sample. Data were analyzed using simple and multiple correlation techniques via SPSS, with a 95% confidence level (α = 0.05). The results reveal three key findings: (1) Physical condition has a statistically significant relationship with short-serve performance (r = 0.828; p < 0.05), accounting for 68.5% of the performance variation. (2) Concentration also shows a significant effect (r = 0.843; p < 0.05), contributing 71.1%. (3) When combined, physical condition and concentration have a significant joint contribution to short-serve performance (R = 0.871; p = 0.031 < 0.05), explaining 75.8% of the variance. The analysis indicates the probability of these results occurring by chance is low, and therefore, the influence of the variables is considered reliable and meaningful in a statistical sense. These findings highlight the importance of both physical readiness and mental focus in improving badminton skills at the elementary level. Future research is recommended to explore additional factors, such as coaching methods or motivation, that may also impact badminton performance, and to expand the study to a larger and more diverse student population.